PENEGAKAN HUKUM PIDANA PERLINDUNGAN DAN PENGELOLAAN LINGKUNGAN HIDUP (UNDANG-UNDANG NOMOR 32 TAHUN 2009) DALAM KASUS PEMBAKARAN HUTAN DAN LAHAN DI KABUPATEN KUTAI TIMUR - Mario Moa (Universitas 17 Agustus 1945 Samarinda, 2020)
ABSTRACT East Kutai Regency has several comparative advantages namely wide land, diverse natural resources that are diverse and supported by strategic geographical position. All the wealth of natural resources and the potential that exists in Kutim Regency will be more meaningful for the lives of present and future generations. The birth of Law Number 32 of 2009 brings new hope in environmental criminal law enforcement, because criminal law enforcement in this Law introduces the threat of minimum punishment in addition to maximum, expansion of evidence, punishment for violations of quality standards, integrated criminal law enforcement, and regulation of corporate crime. Referring to the legislation of natural resources whose estuary is based on the provisions of Law Number 32 of 2009 concerning the protection and management of the environment. Criminal law enforcement in Law 32 of 2009 concerning Environmental Protection and Management in the case of forest and land fires in Kutim District can be subject to Article 108 of Law Number 32 of 2009 concerning Environmental Protection and Management with a minimum of 3 (three) year and no later than 10 (ten) years and a fine of at least Rp. 3,000,000,000.00 (three billion rupiahs) and a maximum of Rp. 10,000,000,000.00 (ten billion rupiahs). The efforts of the East Kutai Government to prevent forest and land fires in Kutim Regency by disseminating information that the burning of land is a criminal form and can be subject to criminal and civil sanctions as stipulated in Article 108 and Article 88 of Law Number 32 of 2009 concerning Environmental Protection and Management and the Province of East Kalimantan has also issued a Regional Regulation on Land and Forest Fire Control. In order to prevent further damage to forests and air pollution as a result of forest and land fires, it is expected that the regional government apparatus should be given a supervisory role and the authority to take action against firefighters who deliberately burn, and are also expected in the contents of Regional regulations on Forest fires. Legal sanctions should be included on the perpetrators, and should be carried out appropriately so as to have a deterrent effect on people who do not pay attention to the provisions of the intended regional regulations, thus, this will make little by little every year forest and land fires can be reduced, if the provisions in the regulation not subject to sanctions, then the rules are just regulations